(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
Contemporary literary and non-literary mapuche production in art such as poetry, short stories, drawings and play performances among others, refer to a variety of discourses joined around a cultural project under transverse common characteristics. These facts allow us to think about a cultural aesthetic system of their own but different on the basis of their background which works as a proposal opposing the hegemonic asymmetrical intercultural context. Our aim is to evaluate how these artistic projects put into operation communicative and discursive elements according to cultural tradition and visibility.